Analisis Perhitungan Harga Pokok Produksi Metode Full Costing dan HPP Penjualan Pada UMKM Mie Ayam Ronggo - Ike Wahyu Eka Safitri; Amelia Kartika Sari; Faikotul Hikmah; Dayinta Puspa Nala; Festi Syahputri Lutfiana; Achmad Rafly Cadafi; Dian Fahriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The goals of this study is to assess the expenses associated with the production of goods at Mr. Lamadi's ronggo chicken noodle umkm located on Jl. Manunggal Amd, Patoman, Pangkemiri, Kec. Tulangan, Sidoarjo Regency. This study employs a descriptive qualitative approach, utilizing samples selected based on primary data. The outcome of this study reveal the production cost of goods on chicken noodles for chicken noodle toppings and pentol amounting to Rp. Rp. 9.500, for the retail price of Rp 14.500 then for chicken feet noodles of Rp. Rp. 8.000 for a retail price of Rp. 12.000 and for original chicken noodles Rp. 7,500 with a retail price of Rp. 11,500. In this analysis, there is a price distinction between the COGS calculation and the selling price of chicken noodles at the market price.